Matching with slot-specific priorities: theory - Scott Duke Kominers; Tayfun Sönmez (Theoretical Economics, 2016)
We introduce a two-sided, many-to-one matching with contracts model in which agents with unit demand match to branches that may have multiple slots available to accept contracts. Each slot has its own linear priority order over contracts; a branch chooses contracts by filling its slots sequentially, according to an order of precedence. We demonstrate that in these matching markets with slot-specific priorities, branches' choice functions may not satisfy the substitutability conditions typically crucial for matching with contracts. Despite this complication, we are able to show that stable outcomes exist in the slot-specific priorities framework and can be found by a cumulative offer mechanism that is strategy-proof and respects unambiguous improvements in priority.
Keywords: C78; D47; D63; D78; 330; Market design; matching with contracts; stability; strategy-proofness; school choice; affirmative action; airline seat upgrades